RETRACTED: Pelatihan Kebersyukuran; Sebuah Upaya untuk Menurunkan Kecemasan Menghadapi Ujian Nasional pada Siswa SMA - Mukhlis, Hamid (Universitas Aisyah Pringsewu, 2016)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Aisyah: Jurnal Ilmu Kesehatan to article entitled “Pelatihan Kebersyukuran; Sebuah Upaya untuk Menurunkan Kecemasan Menghadapi Ujian Nasional pada Siswa SMA” Vol 1, No 1, pp. 09-18, June 2016, DOI: http://doi.org/ 10.30604/jika.v1i1.3.This paper has been found to be in violation of the Jurnal Aisyah: Jurnal Ilmu Kesehatan Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Gadjah Mada Journal of Professional Psychology (GamaJPP), Vol. 1, No. 3 (2015), pp. 203-215, entitled